Implementasi Laboratorium Komputer Virtual Berbasis Cloud – Kelas Pemrograman Berorientasi Obyek - Dwi Susanto; Ridi Ferdiana; Selo Sulistyo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2022)
The COVID-19 pandemic that has been occurred since March 2020 has forced learning activities to be carried out online. Online learning activities can generally be done using a learning management system (LMS) and video conference applications. However, in some subject topics, practicum activities are needed, such as in practicum using a computer laboratory. To accomplish computer practicum activities during the pandemic, a computer laboratory that can be accessed online is required. One of the online practicum solutions is a virtual laboratory (Vlab), which is a virtual computer laboratory that uses virtualization technology. Vlab provides a virtual machine (VM) that is accessed online with a remote access application (Remote Desktop Protocol/RDP, Virtual Network Computing/VNC, Secure Shell/SSH). Vlab infrastructure can either use on-premise or public cloud infrastructure. Compared to on-premise infrastructure-based Vlab, public cloud-based Vlab does not require an expensive initial investment and eliminates routine complex hardware maintenance. This study proposes a cloud-based Vlab application with Azure Lab Services in the case of an Object-Oriented Programming class. Vlab was designed based on the technical needs of the programming practicum, which included VM specifications (CPU, RAM, and storage), operating system, and software that must be installed up to the number of VMs in one class. Based on the total cost of ownership analysis, the cost of providing cloud-based Vlab was potentially up to 26% cheaper than on-premise infrastructure-based Vlab. A cloud-based Vlab installation performed using a Powershell script could be completed in six interactions and an installation time of 132 minutes. Vlab access could be done with a standard computer/laptop with an internet connection and an RDP client application. The bandwidth required to access a cloud-based Vlab ranged from 0.13 Mbps to 3.09 Mbps. The bandwidth range is still within the average speed range of the 4G networks available in Indonesia.